Assessment of the Influence of Demographic and Professional Characteristics on Health Care Providers' Pain Management Decisions Using Virtual Humans. Issue 5 (1st May 2016) - Boissoneault, Jeff; Mundt, Jennifer M.; Bartley, Emily J.; Wandner, Laura D.; Hirsh, Adam T.; Robinson, Michael E.
Abstract : Disparities in health care associated with patients' gender, race, and age are well documented. Previous studies using virtual human (VH) technology have demonstrated that provider characteristics may play an important role in pain management decisions. However, these studies have largely emphasized group differences. The aims of this study were to examine dentists' and physicians' use of VH characteristics when making clinical judgments (i.e., cue use) and to identify provider characteristics associated with the magnitude of the impact of these cues (β‐weights). Providers (N=152; 76 physicians, 76 dentists) viewed video vignettes of VH patients varying in gender (male/female), race (white/black), and age (younger/older). Participants rated VH patients' pain intensity and unpleasantness and then rated their own likelihood of administering non‐opioid and opioid analgesics. Compared to physicians, dentists had significantly lower β‐weights associated with VH age cues for all ratings (p<0.001; d>0.69). These effects varied by provider race and gender. For pain intensity, professional differences were present only among non‐white providers. White providers had greater β‐weights than non‐white providers for pain unpleasantness but only among men. Provider differences regarding the use of VH age cues in non‐opioid analgesic administration were present among all providers except non‐white males. These findings highlight the interaction of patient and provider factors in driving clinical decision making. Although profession was related to use of VH age cues in pain‐related clinical judgments, this relationship was modified by providers' personal characteristics. Additional research is needed to understand what aspects of professional training or practice may account for differences between physicians and dentists and what forms of continuing education may help to mitigate the disparities.